Land Use Land Changes in Land Area of Dehradun City, Uttarakhand, India: Analysis Using Digital Maps and Remote Sensing Techniques - Agarwal, Bindu; Kulkarni, Satish; Sharma, Aanchal; Agarwal, Simran (International Journal of Computer Sciences and Engineering, 2025)
After 2000 revolutionary changes have been seen in Dehradun city that time Dehradun formed the capital of Uttarakhand state. A sizable amount of immigration from rural areas and nearby adjoining states such as Uttar Pradesh, Haryana, Punjab, and Delhi has also resulted in the gradual expansion of Dehradun city. Earlier Dehradun was famous for its Litchi fruit & good quality rice grains. Almost up to the year 1990 exporting litchi and rice to all the parts of India and now the condition of the city is that even the people of Dehradun not get sufficient supply. It is due to decreasing agriculture land, the cultivation is affected. The aim of this paper is to recognize changes in built-up areas and open areas of Dehradun city using the geographical information system to analyze land use changes of the period 1998, 2008 & 2017. To achieve the objectives three digital images The satellite image downloaded from earth explorer USGS of the year 1998, 2008 & 2017 has been taken to calculate the areas of three main categories they are built-up, vegetation & non-built-up area. The areas changes in three years gap 1998-2008, 2008-2017 and 1998-2017 have been calculated. The downloaded images converted into shape files of the study area as per Dehradun municipal map 2011 using Arc GIS10.3 and last ERDAS for classification of buildup and open areas. The researcher found a lot of changes in these categories. One category decreases with the time where other increases. There is a lot of new development occurred during the two later periods i.e. 1998-2008 & 2008-2017. In the period 1998-2008 vegetation area decreases 15.31% from overall vegetation where built-up 8.89% increases and 6.41% non-built-up area increases. (Refer to Table 5.2 graph 5.5). In the period 1998-2017 the 38.36% vegetation decreases. Where built area increases prominently 32.45% from the year 1998 and 5.91 % increase in non-built-up area. The result of the study shows the open area is decreased and built up area is increased in the last 20 years